Electron Dynamics Associated With Advection and Diffusion in Self‐Consistent Wave‐Particle Interactions With Oblique Chorus Waves - Huayue Chen; Xueyi Wang; Hong Zhao; Yu Lin; Lunjin Chen; Yoshiharu Omura; Rui Chen; Yi‐Kai Hsieh (Geophysical Research Letters)
Abstract Chorus waves are intense electromagnetic emissions critical in modulating electron dynamics. In this study, we perform two‐dimensional particle‐in‐cell simulations to investigate self‐consistent wave‐particle interactions with oblique chorus waves. We first analyze the electron dynamics sampled from cyclotron and Landau resonances with waves, and then quantify the advection and diffusion coefficients through statistical studies. It is found that phase‐trapped cyclotron resonant electrons satisfy the second‐order resonance condition and gain energy from waves. While phase‐bunched cyclotron resonant electrons cannot remain in resonance for long periods. They transfer energy to waves and are scattered to smaller pitch angles. Landau resonant electrons are primarily energized by waves. For both types of resonances, advection coefficients are greater than diffusion coefficients when the wave amplitude is large. Our study highlights the important role of advection in electron dynamics modulation resulting from nonlinear wave‐particle interactions.